STUDY OF SOME HEMATOLOGICAL VALUES IN HORSES - ΣΚΟΥΝΤΖΟΣ Κ.; ΠΑΠΑΔΙΑ Α.; ΚΑΤΣΙΓΙΑΝΝΗ Σ.; ΒΛΑΙΚΙΔΗΣ Ν.; ΠΡΩΤΟΠΑΠΠΑΣ Θ.; ΡΑΝΤΣΙΟΣ Α. (Journal of the Hellenic Veterinary Medical Society, 1972)
Hematological examinations in 149 clinically healthy horses were made in exploring latent anemias. The values produced may be of use in evaluating hematological findings when following the techniques cited.